Patient Demographic and Socioeconomic Factors Associated With Physical Therapy Utilization After Uncomplicated Meniscectomy. (11th July 2022) - Mercier, Michael R.; Galivanche, Anoop R.; Wiggins, Anthony J.; Kahan, Joseph B.; McLaughlin, William; Radford, Zachary J.; Grauer, Jonathan N.; Gardner, Elizabeth C.
Abstract : Introduction: The extent to which physical therapy (PT) is used after meniscectomy is unknown. The objective of this study was to estimate the extent to which PT is implemented after meniscectomy and to identify factors associated with its utilization. Methods: The Mariner PearlDiver database was queried to identify patients who underwent uncomplicated meniscectomy. The number of PT visits for each patient was tabulated. Logistic regressions were used to compare demographic factors associated with no use of PT and use of nine or more PT visits. Results: In total, 92, 291 patients met inclusion criteria. Of these patients, 72.21% did not use PT and 27.8% used 1 or more PT visits. Of the patients who used PT, 19.76% had 1 to 8 PT visits and 8.03% had 9 or more PT visits. Older age and noncommercial insurance types were associated with no PT use. Male sex, Medicaid, and Medicare were associated with markedly lower odds of increased PT utilization. Conclusion: PT is used in the minority of the time after meniscectomy. Among patients who do use PT, however, notable variation exists in the amount of PT visits used. Patient age, sex, insurance status, and geographic variables were independently associated with PT utilization.